GREEN TECHNOLOGIES IN SMALL BUSINESS: DEVELOPMENT AND IMPLEMENTATION PROSPECTS - Sergiy B Kholod; Vadim V. Tatarinov; Vadim S. Tatarinov (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The article considers the prospects of green technologies, the state and factors hindering their further development in Ukraine. Proposals for the development of green technologies in Ukraine for expanding the participation of small businesses in this process are provided. It has been established that the transition from the traditional model of economic growth to the model of green growth, which provides a high level of production and employment, as well as a fair distribution of income without harming the environment, contributes to sustainable economic development. Based on expert estimates, it is proven that green technologies will become leading in the XXI century. As a result, a small business belonging to a mobile institution can effectively implement green technologies, thus solving a wide range of problems related to its development. It is known that Ukraine is one of the ten countries in the world that produce the largest amount of solid waste. Much of the solid waste from households is dumped in landfills and cannot be recycled and reused due to the complexity of their separate collection, which exacerbates the problem. Small businesses are involved in the process of efficient recycling of solid waste, starting from the stage of preparation for recycling and ending with the process of their disposal. The experience of waste recycling in a closed-cycle economy as part of Industry 4.0, which is characterized by minimizing the negative impact on the environment, is considered. Issues related to solid waste management are considered. Difficulties in the processing of secondary raw materials were highlighted, including the shortage of secondary raw materials in the country and the need to import them, as well as the lack of waste sorting and the necessary containers for the collection of separated waste. The conditions for encouraging the sorting of household waste from the standpoint of environmental and economic feasibility are presented. Measures have been proposed to introduce closed-loop green technologies in Ukraine and involve small businesses (especially in the management of solid and organic household waste), including: bringing legislation in line with the requirements of the closed-loop economy (separate collection of household waste); conducting organizational and educational activities in society to organize separate collection of household waste; ensuring the production of technical means for their separate assembly.